2013
DOI: 10.2337/db12-0981
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 Regulates the Glucagon Response to Fasting and Starvation

Abstract: Glucagon is important for maintaining euglycemia during fasting/starvation, and abnormal glucagon secretion is associated with type 1 and type 2 diabetes; however, the mechanisms of hypoglycemia-induced glucagon secretion are poorly understood. We previously demonstrated that global deletion of mitochondrial uncoupling protein 2 (UCP2−/−) in mice impaired glucagon secretion from isolated islets. Therefore, UCP2 may contribute to the regulation of hypoglycemia-induced glucagon secretion, which is supported by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 46 publications
(66 reference statements)
5
53
2
Order By: Relevance
“…1F). Consistent with the lack of hypothalamic genetic deletion in this model as shown here and previously by others (7,11), centrally regulated metabolic parameters, such as body weight and food intake, were not significantly different between genotypes (Fig. 1C and D).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…1F). Consistent with the lack of hypothalamic genetic deletion in this model as shown here and previously by others (7,11), centrally regulated metabolic parameters, such as body weight and food intake, were not significantly different between genotypes (Fig. 1C and D).…”
Section: Resultssupporting
confidence: 72%
“…GLUcre + Pten fl/fl mice were born in a Mendelian ratio without any apparent postnatal abnormalities. Previous studies by others and our group using the same GLUcre + mice reported an efficient recombination rate (.85% a-cells) (7,11,18). To confirm the efficacy of the gene disruption, we coimmunostained glucagon with cre recombinase and then PTEN in dispersed islet cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane potential recordings and whole cell patchclamp Plasma membrane potential and voltage-dependent K channel activity was measured using a perforated patch technique in whole cell configuration as described previously [31,32] (ESM Methods). 13 C 5 ]glutamine for the indicated times and compared with starved and unlabelled carbon source samples.…”
Section: Nad(p)h Autofluorescence Imagingmentioning
confidence: 99%